Identifying key performance indicators for oil and gas projects in India - Das, Madhumita; Khanapuri, Vivekananda B. (International Journal of Engineering and Technology, 2023)
The primary goal of every project and management team is to accomplish a successful project outcome. Establishing a baseline for performance measurement is the first step in effective project control and management for achieving success. Despite wide-ranging research in this area, there is still a lack of understanding of project success or performance, especially in practice, due to the context-specific and multi-dimensional nature of the project success. Thus, the paper aims to broaden the understanding of project success and to identify the relevant performance indicators for the Oil and Gas (O&G) infrastructure projects towards success in the context of India. Qualitative research was conducted based on reflective focus group interviews with O&G project practitioners to comprehend their opinions of project performance or success. The findings indicate that the thriving areas of project performance no longer depend solely on traditional key performance indicators (KPIs) like time, cost, scope, or quality, but also on other KPIs such as safety, environment, and business & organization performance. The study is expected to enhance the current knowledge by improving comprehension of project success and identifying key performance indicators for O&G projects in India. The study's managerial implication is to guide project managers and core team members in driving the overall success of O&G projects in India, which goes beyond the conventional view of project success. The findings of the paper can offer valuable insights in general for improving project performance in infrastructure and construction management.